Meta Analisis Pengaruh Model Terhubung Terhadap Kompetensi Pengetahuan Siswa SD dan SMP - N, Annisa; Hidayatullah, Silmi; Usmeldi, Usmeldi (Jurnal Penelitian Pembelajaran Fisika, 2021)
Science and twchnology developed rapidly in the 21st century. The 21st century demandedÂ  thatÂ  human have a broad outlook especially in the world of education. The 2013 curriculum was created to face the challenges of the 21st century and aims to increase students' mindset and conceptual mastery of learning material. Integrated learning can combine a concept with other concepts and can be integrated into learning in schools so that it can realize educational goals. However, in reality the teacher's understanding of integrated learning is still limited. One of the solutions to overcome this problem is by conducting a meta-analysis of the effect of the connected model on student learning outcomes. The type of research used is meta-analysis. Meta analysis is a research conducted by summarizing, reviewing and analyzing research data from several pre-existing research results. The articles of this research consist of 25 articles. The Articles are made up of accredited international and national journals. Based on the data analysis, four research results can be stated. First, the application of the connected model has a high effect on learning outcomes at the primary and junior high school levels. Second, the application of the connected model has a meaningful effect on Science, Social Sciences, and Mathematics in SD. Third, the connected learning model has a significant effect on learning outcomes in junior high school science learning materials. Fourth, the application of the connected learning model has a high effect on student cognitive learning outcomes with an average effect size of 1.60. So, it can be concluded that the connected model has a significant effect on student knowledge competencies.